Effectiveness and impact of rotavirus vaccines in Europe, 2006–2014. Issue 18 (27th April 2015) - Karafillakis, Emilie; Hassounah, Sondus; Atchison, Christina
Highlights Seven European countries have implemented rotavirus vaccination at a national level. Vaccine effectiveness against rotavirus ranges from 68% to 98% in Europe. Reductions in rotavirus hospitalisations ranged from 65% to 84% in Europe. Our results confirm the public health benefit of rotavirus vaccination in Europe. Our results support the implementation of universal rotavirus vaccination in Europe.